Fatal late-onset CAR T-cell-mediated encephalitis after axicabtagene-ciloleucel in a patient with large B-cell lymphoma - Jung, Susanne Claudia; Greiner, Jochen; Harsdorf, Stephanie von; Popović, Pavle; Moll, Roland; Schittenhelm, Jens Florian; Kandilaris, Kosmas; Daniel, Volker; Kunz, Alexander; Schmitt, Michael; Dreger, Peter (Blood advances, 2021)
Treatment with CD19-directed (CAR) T cells has evolved as a standard of care for multiply relapsed or refractory large B-cell lymphoma (r/r LBCL). A common side effect of this treatment is the immune effector cell-associated neurotoxicity syndrome (ICANS). Severe ICANS can occur in up to 30% to 40% of patients treated with axicabtagene-ciloleucel (axi-cel), usually within the first 4 weeks after administration of the dose and usually responding well to steroids. We describe a case of progressive central neurotoxicity occurring 9 months after axi-cel infusion in a patient with r/r LBCL who had undergone a prior allogeneic hematopoietic cell transplant. Despite extensive systemic and intrathecal immunosuppression, neurological deterioration was inexorable and eventually fatal within 5 months. High CAR T-cell DNA copy numbers and elevated levels of interleukin-1 (IL-1) and IL-6 were found in the cerebral spinal fluid as clinical symptoms emerged, and CAR T-cell brain infiltration was observed on autopsy, suggesting that CAR T cells played a major pathogenetic role. This case of unexpected, devastating, late neurotoxicity warrants intensified investigation of neurological off-target effects of CD19-directed CAR T cells and highlights the need for continuous monitoring for late toxicities in this vulnerable patient population.
Gesehen am 15.12.2021